(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
Currently, many buildings in Ukraine are affected by significant dynamic loads associated with military operations on the territory of the country. In practice, this can lead to the so-called progressive destruction, however, unlike static loads, shock-explosive loads require an assessment of not only the mechanical characteristics of the building, but also an assessment of its own dynamic characteristics. Such characteristics traditionally include the spectrum of natural frequencies and the forms of oscillations corresponding to them. However, the assessment of dynamic characteristics must be preceded by an assessment of the static performance of the building. Unfortunately, the specialized professional and reference literature lacks data on the dynamic operation of most types of buildings, including multi-story buildings with a steel frame. Therefore, such a task will be formulated and solved in the course of research. The obtained results of the static analysis confirmed the correctness of the accepted cross-sections of the main load-bearing elements of the steel frame of the building. The outermost columns of the frame were the most loaded, the cross-sections of which were recommended to be increased. As additional recommendations, it was proposed to replace rolled profiles with universal welded ones made of hot-rolled sheet steel. This will simplify the construction of nodal connections of the frame, which, in turn, will increase the level of its overall reliability. The dynamic analysis made it possible to reveal a rather dense spectrum of the lower natural frequencies of the frame, which lie in the range of up to 5 Hz. The corresponding lower forms of self-oscillations include the entire steel frame of the building in the work, which helps to reduce the amplitudes of its oscillations.